Pemanfaatan Karaginan Setengah Jadi untuk Pembuatan Pasta Gigi - Sri Istini; Achmad Zatnika (Fakultas Farmasi Universitas Pancasila, 2004)
Carrageenan, a substance of seaweeds made from carrageenophyte, consists of kappa, iota and lamda form. Semi-refined carrageenan can be used as stabilizer, emulsifier, and the thickening agent in industries such as pharmaceutical and cosmetic industries. Tooth paste as a cosmetic product requires a thickening agent in the preparation. In this experiment, semi-refined carrageenan: iota (I) and kappa (K) were used in several concentrations; 0.2, 0.4, 0.6 and 0.8 % and in combination: A(I: K=90: 10), B(I:K=70:30), C(I:K=50:50), D(I:K=30:70), E(I:K=10:90). The determination was based upon organoleptic, physical and chemical analysis. The obtained results showed that 0.8% of combination D gave the best results with some results fulfilling the SNI requirements.